Donor-Recipient Size Mismatch in Paediatric Renal Transplantation - J. Donati-Bourne; H. W. Roberts; R. A. Coleman (Journal of Transplantation)
Introduction. End stage renal failure in children is a rare but devastating condition, and kidney transplantation remains the only permanent treatment option. The aim of this review was to elucidate the broad surgical issues surrounding the mismatch in size of adult kidney donors to their paediatric recipients. Methods. A comprehensive literature search was undertaken on PubMed, MEDLINE, and Google Scholar for all relevant scientific articles published to date in English language. Manual search of the bibliographies was also performed to supplement the original search. Results. Size-matching kidneys for transplantation into children is not feasible due to limited organ availability from paediatric donors, resulting in prolonged waiting list times. Transplanting a comparatively large adult kidney into a child may lead to potential challenges related to the surgical incision and approach, vessel anastomoses, wound closure, postoperative cardiovascular stability, and age-correlated maturation of the graft. Conclusion. The transplantation of an adult kidney into a size mismatched paediatric recipient significantly reduces waiting times for surgery; however, it presents further challenges in terms of both the surgical procedure and the post-operative management of the patient’s physiological parameters.